Why is Parfois not selling as weel in Germany and Austria as in other countries? A problem-based analysis of the Portuguese accessory brand Parfois in the German and Austrian market - Dilig, Ina Gabriele (2018)
The fashion accessories brand Parfois is facing difficulties in the German and Austrian market. Low traffic and conversion rates in current operations hinder the brand to expand its store network. This Work Project aims to identify potential issues and local consumer preferences and derive marketing recommendations to increase future sales and enable a more effective allocation of the marketing budget. A triangulation methodological approach combined in-store observations and qualitative in-depth interviews with consumers and employees, identifying low awareness and ineffective communication, inconvenient locations and a discrepancy between the target and actual visitors as critical issues. The primary recommendation is to attract and bond the millennial generation.